The role of human leukocyte antigen in HTLV-1 infection and progression to ATLL and HAM/TSP: a systematic review and meta-analysis - Shayan Mardi; Maryam Rashidian; Fatemeh Bastan; Ghazale Molaverdi; Sayed-Hamidreza Mozhgani (Virology Journal)
Abstract Background Human T-cell lymphotropic virus type 1 (HTLV-1) is a retrovirus that leads to lifelong infection and multiple diseases, including HAM/TSP and ATLL. Despite extensive research, the exact pathophysiology of HTLV infection and its related diseases is enigmatic. In this study, we aimed to review and analyze the effect of different HLA alleles as protective or predisposing factors in HTLV-1 infection and its progression to related diseases. Method Three databases (PubMed, Web of Science, and Scopus) were searched for eligible studies. Twenty-five papers with 7279 participants were included in the quantitative analysis. The relevant data were extracted, and 198 meta-analyses were conducted on each reported HLA and population. Results The results of our investigation suggest 3 HLAs with preventive effects against HTLV infection, including HLA-B*35, DRB1*09, and DRB1*16. Also, HLA-DQB1*05:01 might prevent HTLV progression to ATLL. In contrast, HLA-DRB1*13 is more prevalent in ATLL patients than HTLV carriers. Additionally, our results propound that carriers of HLA-A*28, B*54, C*07, DQB1*03:01, and DRB1*07:01 are at higher risk, and carriers of HLA-A*30, B*37, B*40, B*44, C*08, DQB1*06:02, and DRB1*15:01 are in lower risk of HTLV progression to HAM/TSP. We concluded that the mentioned HLA alleles are potential biomarkers of HTLV infection and its progression to related diseases.